RELATIONSHIP BETWEEN RED DISTRIBUTION WIDTH (RDW) AND PEDIATRIC APPENDICITIS SCORE (PAS)IN DETERMINING THE SEVERITY DEGREE OF ACUTE APPENDICITIS IN CHILDREN IN H. ADAM MALIK HOSPITAL MEDAN - Khairil Munandar Hasibuan (International Journal of Research Science and Management, 2020)
Introduction: One of the sign of inflammation are the red distribution width (RDW) and neutrophils lymphocyte ratio (NLR). The width of the distribution of red blood cells (RDW) is a measure of the size of circulating erythrocytes. We aim to assess the association of RDW with pediatric appendicitis score (PAS) to determine the severity degree of acute appendicitis in children. Material Methods: A non-experimental study using a retrospective descriptive method was conducted at the Department of Surgery in the Pediatric Surgery Division of the H. Adam Malik Hospital in Medan with data taken based on the medical records of inpatients and outpatients ≤ 18 years old with a diagnosis of acute appendicitis at the H. Adam Malik General Hospital from January 2015 to December 2017. Data to be collected, processed, and analyzed descriptively. Result: From the data, showed that of the 40 patients who became the study sample consisted of 28 men (70%) and 12 women (30%). The median age of all samples in this study was 11 years, with the youngest being 0 years to the most mature is 18 years. For the median value of the distribution of red blood cells (RDW) is 12.95 with a minimum value of 11.50 and a maximum value of 18.30. Whereas the median value of Pediatric Appendicitis Score (PAS) is 4.50 with a range of values from 1 to 9. Conclusion: We found that the relationship between red blood cell distribution (RDW) and pediatric appendicitis score (PAS) were statistically significant, which were analyzed using Spearman correlation data analysis with correlation results (r) = 0.508 and p value of 0.001.